Partisipasi Masyarakat dalam Pencegahan Covid-19 - Hermawan, Yudan; Rofiq, Akhmad (Journal of Nonformal Education and Community Empowerment, 2020)
COVID-19 is rapidly expanding and is becoming a global issue affecting all sectors of life. World Health Organization (WHO) has applied this virus as a global pandemic. Community participation is needed in the prevention of the virus. Bejiharjo Village participated in the prevention of covid-19 to create the Covid-19 Task Force. The purpose of this study was to determine: the stages and forms of community participation in the prevention of COVID 19 in Bejiharjo Village, Karangmojo, Gunungkidul. Qualitative research with case study methods. Collecting data using interview techniques, observation, and documentation. The validity of the data used was the persistence technique of field observations, triangulation of sources and methods. Data analysis used an interactive model, namely data reduction, presentation and drawing conclusions. The results of the study are the stages of community participation starting from the process of planning, implementing, evaluating and utilizing the results.